Grid integration of electric mobility : 1st International ATZ Conference 2016 - Liebl, Johannes (Springer Vieweg, 2016)
The UN Climate Change Conference in Paris, with its key topics of global warming and deteriorating air quality, will speed up the advance of electric mobility. CO2-neutral and zero-emission mobility require electricity to be generated from regenerative sources of energy. Power generation from wind and solar energy, however is dependent on the weather and is therefore not stable. The irregularities that occur in nature can result in unacceptable voltage fluctuations in the power grid. For that reason, the availability of highly flexible loads and storage systems is becoming particularly important. Electric vehicles, with their grid-relevant properties as controllable power consumers and electricity storage systems, could help to stabilize future power grids. Contents Markets.- Traffic and energy systems.- Local energy systems.- Information and communication technology.- System behavior.- Overall energy systems II. Target audiences Automotive engineers and chassis specialists as well as students looking for state-of-the-art information regarding their field of activity - Lecturers and instructors at universities and universities of applied sciences with the main subject of automotive engineering - Experts, researchers and development engineers of the automotive and the supplying industry Publisher ATZlive stands for top quality and a high level of specialist information and is part of the worldwide specialist scientific publishing group Springer Science + Business Media.
Keywords: Electric vehicles -- Congresses.; Smart power grids -- Congresses.; Electric power transmission -- Congresses.; elektronické knihy; electronic books